Map1b-Dependent Rac Activation Is Required for Ampa Receptor Endocytosis During Long-Term Depression - Morales-Munoz, B; Rozas-Salas, C; Rojas-Montecinos, P (2013)
The microtubule-associated protein 1B (MAP1B) plays critical roles in neurite growth and synapse maturation during brain development. This protein is well expressed in the adult brain. However, its function in mature neurons remains unknown. We have used a genetically modified mouse model and shRNA techniques to assess the role of MAP1B at established synapses, bypassing MAP1B functions during neuronal development. Under these conditions, we found that MAP1B deficiency alters synaptic plasticity by specifically impairing long-term depression (LTD) expression. Interestingly, this is due to a failure to trigger AMPA receptor endocytosis and spine shrinkage during LTD. These defects are accompanied by an impaired targeting of the Rac1 activator Tiam1 at synaptic compartments. Accordingly, LTD and AMPA receptor endocytosis are restored in MAP1B-deficient neurons by providing additional Rac1. Therefore, these results indicate that the MAP1B-Tiam1-Rac1 relay is essential for spine structural plasticity and removal of AMPA receptors from synapses during LTD. This work highlights the importance of MAPs as signalling hubs controlling the actin cytoskeleton and receptor trafficking during plasticity in mature neurons. © 2013 European Molecular Biology Organization.